Comparison of professionalism between emergency medicine resident physicians and faculty physicians: A multicenter cross-sectional study - Shiga, Takashi (PLoS One, 2020)
Professionalism is a critical competency for emergency medicine (EM) physicians, and professional behavior affects patient satisfaction. However, the findings of various studies indicate that there are differences in the interpretation of professionalism among EM resident physicians and faculty physicians. Using a cross-sectional survey, we aimed to analyze common challenges to medical professionalism for Japanese EM physicians and survey the extent of professionalism coursework completed during undergraduate medical education. We conducted a multicenter cross-sectional survey of EM resident physicians and faculty physicians at academic conferences and eight teaching hospitals in Japan using the questionnaire by Barry and colleagues. We analyzed the frequency of providing either the best or second-best answers to each scenario as the main outcome measure and compared the frequencies between EM resident physicians and EM faculty physicians. Fisher’s exact test and the Wilcoxon rank sum test were used to analyze data. A total of 176 physicians (86 EM resident physicians and 90 EM faculty physicians) completed the survey. The response rate was 92.6%. The most challenging scenario presented to participants dealt with sexual harassment, and only 44.5% chose the best or second-best answers, followed by poor responses to the confidentiality scenario (69.9%). The frequency of either the best or second-best responses to the confidentiality scenario was significantly greater for EM resident physicians than for EM faculty physicians (77.1% versus 62.9%, p = 0.048). More participants in the EM resident physician group completed formal courses in medical professionalism than those in the EM faculty physician group (25.8% versus 5.5%, p < 0.01). Further, EM faculty physicians were less likely than EM resident physicians to provide acceptable responses in terms of confidentiality, and few of both had received professionalism training through school curricula. Continuous professionalism education focused on the prevention of sexual harassment and gender gap is needed for both EM resident physicians and faculty physicians in Japan.